Aspectos de la nueva gestión publica en Colombia (2014)
The no legitimization of some public entities in Colombia has propelled some changes within the parameters of the New Public Management. The Urban Development Institute (IDU), one of the most important institutions of the capital city, by the scandals of corruption and poor implementation has experienced in recent years, has made some management changes within the organization. This paper describes some aspects of these transformations implemented and tries to establish whether they have had a positive effect against the perception that people have, and whether these changes have improved the results should be the entity to the infrastructure that Capital city demand